Search for pair-produced massive coloured scalars in four-jet final states with the ATLAS detector in proton-proton collisions at $\sqrt{s}=7$ TeV - ATLAS collaboration (2912 authors) (2013)
A search for pair-produced massive coloured scalar particles decaying to a four-jet final state is performed by the ATLAS experiment at the LHC in proton–proton collisions at . The analysed data sample corresponds to an integrated luminosity of 4.6 fb(−1). No deviation from the Standard Model is observed in the invariant mass spectrum of the two-jet pairs. A limit on the scalar gluon pair production cross section of 70 pb (10 pb) is obtained at the 95 % confidence level for a scalar gluon mass of 150 GeV (350 GeV). Interpreting these results as mass limits on scalar gluons, masses ranging from 150 GeV to 287 GeV are excluded at the 95 % confidence level.